2021
DOI: 10.3390/min11020216
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Chemical Specificity of Dusts Originating from Iron and Non-Ferrous Metallurgy in the Light of Their Magnetic Susceptibility

Abstract: This study aims at detailed characteristics and comparison between dusts from various iron and non-ferrous metal production processes in order to identify individual mineral phases, chemical composition, and their influence on the values of magnetic susceptibility. Various analytical methods used include inductively coupled plasma optical emission spectroscopy, X-ray diffraction, scanning electron microscopy, and Mössbauer spectroscopy integrated with magnetic susceptibility measurements and thermomagnetic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…10). The sextet fitted with zero quadrupolar splitting and chemical shift likely corresponds to metallic α-Fe (CS = 0 mm/s, H = 33.0 T) (Stevens et al, 2005) and the doublet (CS = 1.04 mm/s, QS = 0.67 mm/s) likely corresponds to Fe 2+ in Wüstite (FeO) (Jabłońska et al, 2021). This is consistent with powder XRD analysis which also indicated the presence of metallic Fe and FeO.…”
Section: Mössbauer Spectroscopysupporting
confidence: 80%
See 1 more Smart Citation
“…10). The sextet fitted with zero quadrupolar splitting and chemical shift likely corresponds to metallic α-Fe (CS = 0 mm/s, H = 33.0 T) (Stevens et al, 2005) and the doublet (CS = 1.04 mm/s, QS = 0.67 mm/s) likely corresponds to Fe 2+ in Wüstite (FeO) (Jabłońska et al, 2021). This is consistent with powder XRD analysis which also indicated the presence of metallic Fe and FeO.…”
Section: Mössbauer Spectroscopysupporting
confidence: 80%
“…Previous work in the literature suggested that 57 Fe Mössbauer spectroscopy can be utilized to detect and differentiate the small amounts of ZnFe 2 O 4 that can be found in steelmaking dusts from spinel more easily than using powder XRD (Jabłońska et al, 2021;Vereš et al, 2010).…”
Section: Mössbauer Spectroscopymentioning
confidence: 99%
“…It is often assumed that anthropogenic Fe-rich particles are mostly spherical (e.g., Choël et al, 2007). It is the common form originating from high temperature processes, but in iron metallurgy dust of different shape, size and chemical composition can be emitted (Jarzębski and Kapała, 1975;Wilczyńska-Michalik 1981;Jabłońska et al 2021). In 1979 Steelworks in Krakow alone emitted dust containing 18 000 tons of Fe (Cole 1991).…”
Section: Size Morphology and Chemical Composition Of Fe-rich Particlesmentioning
confidence: 99%
“…urban dust [16]- [18], soils [19], lake sediments [20]. A wide range of materials, even sometimes very unusual like snow, leaves or spider webs, allow us to study all types of the environment.…”
Section: Introductionmentioning
confidence: 99%